Ecosistema digital de venta de productos para bodegas - Vilcarromero Oliva, Marjorie Del Carmen (2021)
As a result of the pandemic in which we are living, many businesses tried to speed up their technological transformation process in order to mitigate the decrease in their sales; this evidenced many technological shortcomings in our country. The “bodegas” was the most impacted, since by not having a digital ecosystem that allows them to sell their products, they lost many sales by not reaching those people who decided to stay at home. After identifying the current needs, both of “bodeguero” and consumers; the idea was born of creating a comprehensive solution so that “bodegas” can market their products using a 100% digital platform. This platform is made up of a mobile application that includes the following functionalities: • Product Management: which allows the “bodega” to systematize their current inventory process and have better control of the stock of their products. In turn, this allows the consumer to check the availability of products online. • Order Management: which allows adequate control of the delivery and current status of the orders received by the “bodega”, allowing the consumer to have real-time data on the delivery of their order. • Online Payment: which allows payment with any type of card, avoiding the use of cash. As a final result, a product is obtained that helps with the technological development of the “bodegas”; helping them increase their sales by reaching new customers. And on the consumer side, it offers them the possibility of consuming in “bodegas” from the comfort of their home, having the option of validating the availability of products and making the payment online.